Does Changing the Legal Drinking Age Influence Youth Behaviour? - Stefan Boes; Steven Stillman (Institute for the Study of Labor (IZA), 2013)
This paper examines the impact of a reduction in the legal drinking age in New Zealand from 20 to 18 on alcohol use, and alcohol-related hospitalisations and vehicular accidents among teenagers. We use both a difference-in-differences approach and a regression discontinuity design (RDD) to examine the impact of the law change. Our main findings are that lowering the legal drinking age did not appear to have led to, on average, an increase in alcohol consumption or binge drinking among 15-17 or 18-19 year-olds. However, there is evidence that the law change led to a significant increase in alcohol-related hospital admission rates for 18-19 year-olds, as well as for 15-17 year-olds. While these increases are large in relative magnitude, they are small in the absolute number of affected teenagers. Finally, we find no evidence for an increase in alcohol-related vehicular accidents at the time of the law change for any teenagers. In an important methodological contribution, we show that one approach commonly used to estimate the impact of changing the legal drinking age on outcomes, an RDD that compares individuals just younger than the drinking age to those just older, has the potential to give misleading results. Overall, our results support the argument that the legal drinking age can be lowered without leading to large increases in detrimental outcomes for youth.
Keywords: I18; K42; C25; 330; drinking age; alcohol consumption; hospitalization; vehicular accidents; New Zealand